Bond between FRP formworks and concrete-effect of surface treatments and adhesives - Goyal, R.; Mukherjee, Abhijit; Goyal, S. (2016)
Copyright © 2016 Techno-Press, Ltd. FRP stay-in-place (SIP) formworks are designed as a support for casting concrete and as a tension reinforcement when concrete is cured. Bond development between SIP formwork and concrete is critical for FRP tension element to be effective. This paper reports the bond strength between FRP formwork and concrete for different interfacial treatments. A novel experimental setup is prepared for observing the bond behaviour. Three different adhesives with varying workability have been investigated. Along with the load-deformation characteristics, bond slip and strains in the formwork have been measured. A finite element numerical simulation was conducted for the experiments to understand the underlying mechanism. The results show that the adhesive bonding has the best bond strength.